Comparative test of quality in health service delivery among public sector (subsidized scheme) and private (taxable medical system and prepaid) (2013)
The quality of feature health services in Colombia has been most questioned for users as like communications media and the results than has been showed, aren ́t lie. Despite of this, hasn ́t been demonstrated that there is existed an comprehensive analysis where can attack the causes, quality of feature health services on the public sector, hasn ́t depends only Social General Segurity System, also there are many state areas involved: Education and Fianancial (Public Finance), additional, the same participation of users who show in much oportunities ignorance to normative that exists over health theme. Not formulate until improvement plans finals where the quality of feature health services has been sanetized, it won ́t be better and his panorama will go on same.